Some conditions of the non-reducible operators - Stecenko, V.; Curcic, D. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. Я. Стеценко, Д. М. Чурчич. Некоторые признаки неразложимости операторовV. Stecenka, D. Čiurčičius. Kai kurių operatorių neišsklaidomumo požymiai